بررسیِ حرکت¬شناختیِ افعالِ متنِ "ما زِ بالاییم و بالا می رویم" مولانا Kinetic Study of Mewlana Jalaluddin Rumi's "Mazi Balaeem we Bala Mi Roeem" Text's Verbs (Journal of the College of Languages (JCL), 2018)
چکیدهی بحث به نظر میآید که عالم هستی ، بر مسألهی « حرکت» استوار دارد ، و روح ، همیشه دنبال دگرگونی و تکامل و برتری میگردد. حرکت ، همهی چیزها در عالم إمکان را در بر میگیرد. حرکت در بنیادهای فکر مولانا جای مهمی دارد .اشعار مولانا مقدار زیادی از پویایی و حرکت برخوردارست، و از آنجایی که فعل ، عنصر تکانبخش جمله ، و کانون دلالت است ، ترجیح دادیم - علاوه بر دیگر عناصر حرکت مانند حروف اضافه، ضمایر اشاره - افعال متن « ما زِ بالاییم و بالا می رویم» را برای فهم بهتر صورت و محتوای این متن ، مورد بررسی قرار دهیم. ممکن است عناصر حرکت و کانون دلالتِ آن در شکل زیر توضیح دهیم : بحث حاضر به این نتیجهی عمومی رسیده است که حرکت افعال در این قصیده حرکت عروج است . این حرکت صورت می گیرد پس از این که آدمی حقیقت خودش را می شناسد زیرا که او از فهم راز روح که در بدن خود عاجز است پس چطور میتواند به سرّ و ذات حق متعال پی برد . پس شناخت حقیقت وجود ، از راه شناخت نفس آدمی میگذرد . و چون آدمی همیشه در حال حرکت و انتقال و رفتن میباشد، مولانا در تصویر حرکت عارف در غزل حاضر ، علاوه بر حروف اضافه ( از - به) بسیاری فعل ( می رویم ) را به کار برده است . این حرکت در حال ترقی به سوی قلهی کوه قاف و یا به مرتبهی انسان صورت میگیرد. افعال متن حاضر به مجهول بودن مبدأ و معاد وسرنوشت انسان از یک سو ، و از سوی دیگر فنای عاشق در عشق حق تعالی و بقای او در همان عشق اشاره دارد.Abstract The existent world is a kinetic one. Human spirit exerts efforts towards change, development and ascension. Kinesis controls everything in the world of existence. It occupies a crucial position in the thought of Mewlana Jalaluddin Rumi. The verbs used in the poem in question have a good deal of activeness and kinesis. Whereas the verb is the motivating element and the semantic centre of the sentence, the researcher has suggested the examination of the verbs of Mewlana Jalaluddin Rumi's text. Moreover, the researcher has referred to other kinetic elements, such as, conjunctions, demonstrative pronouns and relative pronouns in order to attain to the best understanding of the form and content of the present text. It might be possible illustrate the kinetic elements as follows: The present paper has concluded that the verb kinesis in the poem is an ascent one. This kinesis is achieved when Man identifies the reality of himself because he is unable to know the secret of himself; as such, how could he know the almighty Allah? Whereas Man is in a persistent kinesis, Mewlana, therefore, used the verb "Mi roeem' frequently, not to mention the conjunctions "as: from/ be: to". This kinesis heads to qaf, i. e., the rank of the integrated Man. The verbs stipulated in the text have pointed to the unknown beginning and returning of Man and his extinction in the love of the almighty Allah.